Gothic features in The Turn of the Screw and The Haunting of Bly Manor - Pikhartová, Aneta (Univerzita Pardubice, 2023)
This bachelor thesis provides the cultural and historical context of novella The Turn of the Screw and the TV series The Haunting of Bly Manor, and the literary context of the novella. It then focuses on the Gothic fiction and the distinction between English Gothic fiction and American Gothic fiction. And lastly it analyzes and compares the Gothic features that are present in both of these works.
Gotické prvky v novele The Turn of the Screw a seriálu The Haunting of Bly Manor
Keywords: gotická fikce; gotické znaky; Haunting of Bly Manor; Turn of the Screw; James, Henry; Gothic fiction; Gothic features; Haunting of Bly Manor; Turn of the Screw; James, Henry